Decay Nature of Radionuclide Released From Triga Mark-II Reactor (GUB Journal of Science and Engineering, 2021)
Considering a hypothetical accident, the deposition of radio krypton (85Kr) has been studied that is released from TRIGA MARK-II reactor by its decay behavior. The measurement of radiological ground concentration leads to the study of the emission process of 85Kr nucleus, and the site-specific data related to this measurement have been analyzed later on. In this work, the radioactivity in the reactor core and release rate as well as Gaussian diffusion factor have also been considered. It is observed from the data analysis that the maximum concentration of 85Kr in ground is 1.115E+3 Bq/m2 in South (S) direction. Here, the nuclear binary fission has been presented with the greater probability of production of magic nuclei where the reactions found to be endoergic where a nuclear reaction occurs with the absorption of energy. Doubly magic nuclei like 4He, 16O, 40Ca, and 48Ca have also been identified as fission fragments that follow the nuclear shell closure. The results of this work will be an important guide in the study of radionuclide splitting into several nuclei as well as for accidental scinerio.GUB JOURNAL OF SCIENCE AND ENGINEERING, Vol 7, Dec 2020 P 57-61